2019
DOI: 10.1155/2019/1204709
|View full text |Cite
|
Sign up to set email alerts
|

Baihui Point Laser Acupuncture Ameliorates Cognitive Impairment, Motor Deficit, and Neuronal Loss Partly via Antioxidant and Anti-Inflammatory Effects in an Animal Model of Focal Ischemic Stroke

Abstract: Stroke is recognized as one of the most dangerous killer diseases in Thailand and other countries worldwide. The development of a novel strategy for treating stroke patients is therefore urgently required. The present study investigated the effect of laser acupuncture at the Baihui point on cognitive and functional recovery, neuronal loss, antioxidant enzyme activities, and interleukin-6 (IL-6) activity in the hippocampus in an animal model of focal ischemic stroke. Male Wistar rats were randomly divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
0
27
0
2
Order By: Relevance
“…In addition, AD animal models show deficits in both synaptic morphological plasticity and synaptic transmission (Guo et al, 2017 ; Chakroborty et al, 2019 ). Accumulating evidence has demonstrated that acupuncture may ameliorate synapse and neuron damage caused by ischemic stroke (Jittiwat, 2019 ), inflammation, oxidative stress (Du et al, 2018 ), and neurodegeneration (Zhao Y. et al, 2019 ). Li et al ( 2012 ) reported that acupuncture reduced neuron loss in the hippocampal CA3 and DG areas in SAMP8 mice and attenuated memory impairments.…”
Section: Effects Of Acupuncture On the Pathogenesis And Pathological mentioning
confidence: 99%
“…In addition, AD animal models show deficits in both synaptic morphological plasticity and synaptic transmission (Guo et al, 2017 ; Chakroborty et al, 2019 ). Accumulating evidence has demonstrated that acupuncture may ameliorate synapse and neuron damage caused by ischemic stroke (Jittiwat, 2019 ), inflammation, oxidative stress (Du et al, 2018 ), and neurodegeneration (Zhao Y. et al, 2019 ). Li et al ( 2012 ) reported that acupuncture reduced neuron loss in the hippocampal CA3 and DG areas in SAMP8 mice and attenuated memory impairments.…”
Section: Effects Of Acupuncture On the Pathogenesis And Pathological mentioning
confidence: 99%
“…A recent study showed the effect of laser acupuncture to attenuate memory impairment and facilitate recovery by improving neural density in the hippocampus, showing that it had been reduced in number after cerebral ischemia. This is achieved by laser acupuncture stimulation that increases cAMP response element-binding (CREB) activity by reducing the neuronal cell loss at the hippocampus [ 24 ]. Knowing that, after ischemic stroke, it was shown that neurons necrotize in the infarct core; however, in the surrounding region (the penumbra area), they took hours to days to die after ischemia onset, which provides a possible therapeutic target to rescue the injured neurons from autophagy and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The male Sprague-Dawley rats weighing 270 ± 20 g were housed three to four per cage and maintained on a 12 h light/dark cycle at 23°C with water and food available ad libitum. Animals that were dying before the experimental endpoint were replaced to ensure n = 10 each group for quantification according to some previous studies [ 21 , 22 ]. Body weight was monitored during the whole experiment.…”
Section: Methodsmentioning
confidence: 99%